Allogeneic hematopoietic stem cell transplantation for adult patients with B-cell acute lymphoblastic leukemia with high hyperdiploidy: a retrospective nationwide study. Issue 10 (24th August 2021) - Kurosawa, Shuhei; Kaito, Satoshi; Uchida, Naoyuki; Fukuda, Takahiro; Doki, Noriko; Mori, Takehiko; Hasegawa, Yuichi; Takada, Satoru; Sakaida, Emiko; Tanaka, Masatsugu; Ikegame, Kazuhiro; Kanda, Junya; et al.
Abstract: We compared the transplant outcomes of adult patients with B-cell acute lymphoblastic leukemia characterized by high hyperdiploidy (HeH; 51–65 chromosomes) ( n  = 29) and those with a normal karyotype ( n  = 87) by propensity score-matched analysis. There were no significant differences among groups in 3-year probabilities of overall survival (OS, 63.5% vs. 55.3%, p  = .553), cumulative relapse incidence (28.6% vs. 28.7%, p  = .982), and non-relapse mortality (10.9% vs. 21.4%, p  = .303). Three-year OS was significantly worse in HeH patients with third or later complete remission (CR) or non-CR compared with those in first CR (19.0% vs. 69.9%, p  = .010). Frequently gained chromosomes +21 (75.9%), +4 (69.0%), +6 (69.0%), +10 (69.0%), and +1 (69.0%) had no significant prognostic impact on the OS of patients with HeH in multivariate analyses. Patients with HeH who may benefit from allogeneic hematopoietic stem cell transplantation should be further analyzed.